PERANCANGAN DAN PERENCANAAN PUSAT PENGOLAHAN DAN BUDIDAYA CENGKEH BERBASIS EDUKASI DI DESA UMEJERO, KECAMATAN BUSUNGBIU, KABUPATEN BULELENG: bahasa indonesia - I Putu Adi Jaya Wiguna; I Putu Hartawan; Putri Ayu Devy Permata Sari; Kadek Putra Santika Narayana (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2026)
Buleleng Regency is one of the clove production centers in Bali Province with significant potential to support the local community’s economy, particularly in Umejero Village, Busungbiu District. However, the decline in clove productivity caused by traditional post-harvest processing methods, limited availability of superior seedlings, and the lack of educational facilities for farmers has become a major issue that needs to be addressed. This report discusses the planning and design of an Educational-Based Clove Processing and Cultivation Center in Umejero Village as an integrated solution to overcome these challenges. The purpose of this design is to provide a facility that integrates processing, cultivation, seedling production, research, and educational functions within a well-planned area. This design is expected to improve harvest quality, production efficiency, the availability of superior seedlings, and farmers’ knowledge and skills through sustainable training and educational activities. The design results demonstrate the implementation of the Community Integration with Nature concept through a tropical architectural approach that responds to local climatic and environmental conditions, realized through building mass arrangement, natural ventilation, optimal lighting, and the use of local materials. The presence of this facility is expected to support the sustainability of clove commodities, improve farmers’ welfare, and become a center for clove agribusiness development in Buleleng Regency.